Long-term mercury contamination does not affect the microbial gene potential for C and N cycling in soils but enhances detoxification gene abundance - Frey, Beat; Rast, Basil M.; Qi, Weihong; Stierli, Beat; Brunner, Ivano (Frontiers in Microbiology, 2022)
Soil microorganisms are key transformers of mercury (Hg), a toxic and widespread pollutant. It remains uncertain, however, how long-term exposure to Hg affects crucial microbial functions, such as litter decomposition and nitrogen cycling. Here, we used a metagenomic approach to investigate the state of soil functions in an agricultural floodplain contaminated with Hg for more than 80 years. We sampled soils along a gradient of Hg contamination (high, moderate, low). Hg concentrations at the highly contaminated site (36 mg kg-1 dry soil on average) were approximately 10 times higher than at the moderately contaminated site (3 mg kg-1 dry soil) and more than 100 times higher than at the site with low contamination (0.25 mg kg-1 dry soil; corresponding to the natural background concentration in Switzerland). The analysis of the CAZy and NCyc databases showed that carbon and nitrogen cycling was not strongly affected with high Hg concentrations, although a significant change in the beta-diversity of the predicted genes was observed. The only functional classes from the CAZy database that were significantly positively overrepresented under higher Hg concentrations were genes involved in pectin degradation, and from the NCyc database dissimilatory nitrate reduction and N-fixation. When comparing between low and high Hg concentrations the genes of the EggNOG functional category of inorganic ion transport and metabolism, two genes encoding Hg transport proteins and one gene involved in heavy metal transport detoxification were among those that were highly significantly overrepresented. A look at genes specifically involved in detoxification of Hg species, such as the mer and hgc genes, showed a significant overrepresentation when Hg contamination was increased. Normalized counts of these genes revealed a dominant role for the phylum Proteobacteria. In particular, most counts for almost all mer genes were found in Betaproteobacteria. In contrast, hgc genes were most abundant in Desulfuromonadales. Overall, we conclude from this metagenomic analysis that long-term exposure to high Hg triggers shifts in the functional beta-diversity of the predicted microbial genes, but we do not see a dramatic change or breakdown in functional capabilities, but rather functional redundancy.